A Scoping Review Exploring the Use of Art-Making-as-Therapy in Adult Mental Health Occupational Therapy Practice - Alan Johnson; Samantha Ashby; Miranda Lawry (Scholarworks @ WMU, 2022)
Background: Art-making-as-therapy has been used by occupational therapists in mental health since the inception of the profession. It aims to enable people to gain mastery and produce art. This review synthesizes the research on the use of art-making as therapy by occupational therapists in adult mental health practice. Method: Arksey and O'Malley's 5-stage framework was used. A search of four databases was conducted with the inclusion criteria of papers from 1980 - 2020 using the keywords of occupational therapy, mental health or illness, and art. Thematic analysis was used to analyze the data. Results Results: Of the 847 articles initially identified, 21 were included in the review. Three themes were identified: (a) the benefits of occupational participation in arts-making-as-therapy for consumers, (b) the environmental context of the art-making-as-therapy experience, and (c) using artmaking-as-therapy to inform professional reasoning, including assessing and enhancing therapeutic relationships. The paucity of literature (n = 21) means that results should be interpreted with caution. Conclusion: There is evidence for the benefits of art-making-as-therapy for consumers and occupational therapists in mental health settings. Further research is necessary into the efficacy of using art-making-as-therapy in practice from the perspective of people who live with mental illness.